PERAN KEPOLISIAN DALAM PENINDAKAN KEJAHATAN LINTAS NEGARA DI KAWASAN PERBATASAN INDONESIA-MALAYSIA - Nalindro Nusantoro; Arthur Josias Simon Runturambi; Hendy Febrianto Kurniawan; I Made Chandra Mandira (Halu Oleo University, 2022)
Circulation of narcotics becomes more challenging in the border areas between two countries. In transnational crimes narcotics smuggling is a serious threat to global security. This study aims to determine the actions taken by the Indonesian police in law enforcement and eradicating narcotics smuggling in the border areas of North Kalimantan. This research uses qualitative approach method through interviews with key informants, observations, and supported by literature studies. The data analysis technique uses the opinion of Miles Huberman and Saldana (2014) through stages; data compaction, data presentation (data display), and drawing conclusions or verification (conclusion drawing and verification). Data compaction refers to the process of selecting, focusing, simplifying, abstracting, and transforming data. In depth, this study will discuss the findings of 47 kilograms of drugs smuggled through the Tawau (Malaysia) border through Sebatik (Indonesia). Furthermore, this research is expected to be a pilot in securing other border areas in Indonesia.